2023
DOI: 10.5853/jos.2022.02173
|View full text |Cite
|
Sign up to set email alerts
|

The Heart Is at Risk: Understanding Stroke-Heart-Brain Interactions with Focus on Neurogenic Stress Cardiomyopathy—A Review

Abstract: In recent years, it has been convincingly demonstrated that acute brain injury may cause severe cardiac complications-such as neurogenic stress cardiomyopathy (NSC), a specific form of takotsubo cardiomyopathy. The pathophysiology of these brain-heart interactions is complex and involves sympathetic hyperactivity, activation of the hypothalamic-pituitary-adrenal axis, as well as immune and inflammatory pathways. There have been great strides in our understanding of the axis from the brain to the heart in patie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 175 publications
0
25
0
Order By: Relevance
“…Both regions regulate the central autonomic function and play an integral role in the pathophysiology of the "stroke-heart syndrome." 2,6 In the case of our patient and based on the absence of clinical symptoms, ECG-changes, and wall motion abnormalities, we estimate that cTn-elevation was due to a stroke-induced neurocardiogenic non-ischemic myocardial injury caused either by microcirculatory dysfunction (i.e. endothelial or oxidative stress) or by myocardial demand ischemia precipitated by hypertensive crisis, tachycardia, and respiratory distress.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…Both regions regulate the central autonomic function and play an integral role in the pathophysiology of the "stroke-heart syndrome." 2,6 In the case of our patient and based on the absence of clinical symptoms, ECG-changes, and wall motion abnormalities, we estimate that cTn-elevation was due to a stroke-induced neurocardiogenic non-ischemic myocardial injury caused either by microcirculatory dysfunction (i.e. endothelial or oxidative stress) or by myocardial demand ischemia precipitated by hypertensive crisis, tachycardia, and respiratory distress.…”
Section: Discussionmentioning
confidence: 74%
“…Indeed, it is convincingly recognized that AIS may cause severe cardiac dysfunction, which refers to neurocardiogenic interactions in this population 2 and represents more complex pathophysiological mechanisms than traditional vascular risk factors. 6 Cardiac injury is a common medical problem during the acute phase of AIS 9 and includes a variety of clinical manifestations, that is, post-stroke acute coronary syndromes (ACS; type 1 and 2 myocardial infarction, MI), acute myocardial injury-ischemic and non-ischemic-as presented by cTn-elevation, left ventricular dysfunction of varying severity up to heart failure, and stroke-associated Takotsubo Syndrome, 2 ECG-alterations such as QT-interval prolongation, T-wave inversion, and ST-depression, tachyarrhythmias including atrial fibrillation, 2 and sudden cardiac death. 6 In order to early detect the cardioembolic origin of stroke and to identify patients at high risk of cardiac complications and poor outcomes, quantitative cTn-determination in all patients with suspected stroke is strongly recommended.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[20,21,37,189] Arrhythmias, when coupled with acute hemo-dynamic dysfunction, compromise cerebral perfusion pressure, correlating with elevated post-stroke mortality. [1,126] In a retrospective cross-sectional study from Wira et al, AIS patients admitted from an urban emergency department were assessed within 24 h of symptom onset. Results indicated that troponin elevation, systolic dysfunction, AF, and ischemic changes on ECG may be linked to increased in-hospital mortality rates, highlighting the importance of monitoring cardiac complications in AIS presentation.…”
Section: Cardiovascular Monitoring and Treatment Options After Aismentioning
confidence: 99%